The university as developmental space – a case for thinking differently?. Issue 3 (3rd July 2018) - Gregor, Claire
Abstract: In recent years, there has been a sizeable increase in young people approaching University Counselling and Well-being Services for support in managing mental health difficulties with one research project suggesting an increase of demand upwards of 33%. Support is necessarily often targeted at those who present most 'at risk', but this ignores the potential positive impact that universities can have on promoting mental health for future generations, not least given that nearly half of all young people in the UK participate in Higher Education. Drawing on a case study of one UK undergraduate student, this paper will explore themes common to university students such as difficulties in transitioning from home, defensive-bonding in relationships and low self-esteem. The paper argues the need for universities and colleges to provide ongoing support for students who are 'just about managing' in order to enable them to flourish, both emotionally and academically.